IDENTIFY THE WAYS TO IMPROVE EMPLOYEES’ SKILLS AND CUSTOMER RELATIONSHIP MANAGEMENT OF APPAREL PRODUCT: AN ASSESSMENT OF ONLINE SOCIAL MEDIA CUSTOMER SATISFACTION MEASUREMENT APPROACH (International Journal of Engineering Sciences & Management Research, 2017)
Customer or buyer is the most important part for an online business media. Because of social media can make profit from them. Customer service is one of the major elements for making profit out of the customer. In this research, we have tried to find out by this analysis how to customer service can help to made profit for social media. We have shown that how they could be improved customer service and provided customer satisfaction to build a strong customer relationship (Aghdaie, Tafreshi, & Behzadian, 2014; Madichie, 2014). Through the research, we have discussed the ways of improving customer relationship. This report was mainly showed how to social media could improve employees’ skills and customer relationship management of apparel product.